Nurses' Support for Women with Breast Cancer Undergoing Chemotherapy in Indonesia: A Qualitative Study - Inggriane Puspita Dewi; Anggriyana Tri Widiyanti; Medina Hutami (Journal of Public Health Sciences, 2026)
Women with breast cancer experience multiple biopsychosocial and spiritual challenges during chemotherapy, yet supportive care from nurses in Indonesia remains underexplored. This study aimed to explore nurses' experiences in providing supportive care to women with breast cancer undergoing chemotherapy in Indonesia. A descriptive qualitative design was applied. Six oncology nurses were recruited through purposive sampling in a referral hospital in Bandung, Indonesia. Data were collected using semi-structured interviews and were analyzed thematically following SRQR guidelines. Seven themes with 21 subthemes emerged: (1) psychological support (affirmation, active listening), (2) information and health system support (care pathways, health education, prognosis communication), (3) support for physical needs and daily living (symptom management, activity guidance, collaboration), (4) sexual and intimacy support (partner encouragement, alternatives for sexual needs), (5) spiritual support (facilitating worship, spiritual interventions, clergy guidance), (6) social support (family, community, end-of-life preparation), and (7) barriers (patient/family resistance, lack of training, limited clergy, inadequate facilities). Findings highlight the central role of nurses in delivering holistic supportive care, consistent with Dossey's holistic nursing theory. Addressing gaps in palliative training, spiritual resources, and healthcare infrastructure is critical to strengthening supportive care in Indonesia. Results underscore the need for integrating spiritual and palliative care training into nursing curricula, enhancing interprofessional collaboration, and formulating institutional policies to ensure equitable, holistic cancer care.